Ocular Behçet's Disease: Changing Patterns Over Time, Complications and Long-Term Visual Prognosis. (2nd January 2017) - Accorinti, Massimo; Pesci, Francesca Romana; Pirraglia, Maria Pia; Abicca, Irene; Pivetti-Pezzi, Paola
ABSTRACT: Purpose : To investigate demographic, clinical features and complications of Italian patients with ocular Behçet's disease (BD) over time. Methods : Retrospective study of 385 patients examined from 1968 to 2011, 265 of whom had follow-up ≥ 12 months. Results : A significant increase in the proportion of females ( p = 0.03) and anterior uveitis ( p < 0.001), and a decrease in the complete type of BD in all patients ( p = 0.003) and in males ( p = 0.002), and in hypopyon ( p = 0.024) were observed over time. Optic neuropathy ( p < 0.0001), maculopathy ( p = 0.002), retinal detachment, and retinal neovascularization ( p = 0.02) decreased over time, with no difference between genders, concomitant with an increase in the use of immunosuppressive drugs ( p = 0.003). Visual acuity ≤1/10 was detected more often in males than females ( p = 0.003). Conclusions : A significant shift in clinical manifestations of BD patients was observed over 44 years. Immunosuppressive therapy succeeded in lowering ocular complications. The incidence of ocular BD is increasing in females, but visual prognosis is still worse in males.